Analisis Bentuk dan Hambatan Perlindungan Hukum terhadap Seren Taun Ciptamulya sebagai Ekspresi Budaya Tradisional - Daud Bunar Buwono; Rohaini Rohaini; Dianne Eka Rusmawati; Sepriyadi Adhan S; Muhammad Havez (AHKAM, 2026)
Although the issue of legal protection for Traditional Cultural Expressions (TCEs) has been widely examined, studies that specifically investigate the forms and obstacles of legal protection for Seren Taun Ciptamulya as a TCE belonging to the Masyarakat Hukum Adat Kasepuhan Ciptamulya in Sukabumi Regency remain limited. This study aims to analyze the forms of legal protection for Seren Taun Ciptamulya implemented by the Regional Government of Sukabumi Regency and to identify the obstacles encountered in its implementation. A normative-empirical approach with a descriptive-analytical design was employed, involving two key informants, namely the customary leader of Kasepuhan Ciptamulya and the Head of the Culture and Tourism Office of Sukabumi Regency, selected through purposive sampling. Data were collected through literature study of legislation and relevant scholarship, as well as in-depth interviews, and were analyzed qualitatively. The findings show that legal protection for Seren Taun Ciptamulya is manifested in two main forms: preventive protection through a multi-level regulatory framework comprising the Copyright Law, the Law on Cultural Advancement, government regulations related to communal intellectual property (KIK), and regional regulations; and repressive protection through copyright dispute resolution mechanisms. However, implementation of this protection still faces three principal obstacles: (1) legal substance issues, particularly delays in the formulation of implementing regulations; (2) legal structure issues, including suboptimal coordination between the regional government and the customary community; and (3) legal culture issues, reflected in shifting values and declining commitment among younger generations to safeguarding tradition. The study concludes that synergy between legal substance, structure, and culture is a key prerequisite for effective protection of TCEs, and recommends strengthening coordination between regional government and customary communities as well as accelerating the inventory of TCEs as the basis for participatory and sustainable policy formulation. The implications of this research include theoretical contributions to the development of communal intellectual property law and practical guidance for local governments in designing more responsive protection models for TCEs that are attuned to socio-cultural dynamics, while also opening opportunities for comparative studies with sui generis protection schemes in other countries and with respect to the management of TCE commercialization.